2011
DOI: 10.1182/blood-2010-07-296913
|View full text |Cite
|
Sign up to set email alerts
|

Novel type II anti-CD20 monoclonal antibody (GA101) evokes homotypic adhesion and actin-dependent, lysosome-mediated cell death in B-cell malignancies

Abstract: The anti-CD20 mAb rituximab has substantially improved the clinical outcome of patients with a wide range of B-cell malignancies. However, many patients relapse or fail to respond to rituximab, and thus there is intense investigation into the development of novel anti-CD20 mAbs with improved therapeutic efficacy. Although Fc-Fc␥R interactions appear to underlie much of the therapeutic success with rituximab, certain type II anti-CD20 mAbs efficiently induce programmed cell death (PCD), whereas rituximab-like t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
244
4
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 261 publications
(265 citation statements)
references
References 45 publications
15
244
4
2
Order By: Relevance
“…26 Obinutuzumab not only possesses ADCC activity, but also exhibits multiple MOAs in vitro, including enhanced noncaspase-dependent induction of direct cell death. 25 Similarly, IGN523 possesses multiple mechanisms of action, as shown here in several cell lines in vitro (Fig. 6).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…26 Obinutuzumab not only possesses ADCC activity, but also exhibits multiple MOAs in vitro, including enhanced noncaspase-dependent induction of direct cell death. 25 Similarly, IGN523 possesses multiple mechanisms of action, as shown here in several cell lines in vitro (Fig. 6).…”
Section: Discussionmentioning
confidence: 56%
“…25 To assess whether similar effects are seen with IGN523 plus crosslinker, we investigated if the CD98-IGN523 complex was internalized to lysosomes and whether this led to increased lysosomal permeability (Fig. 5).…”
Section: Ign523 Elicits Caspase-dependent Apoptosis Increases Lysosomentioning
confidence: 99%
“…Also direct cytotoxicity is enhanced. CD20 binding leads to homotypic adhesion and following cell death induction is non-apoptotic, actin-dependent and lysosome mediated [23]. Further in vitro studies showed depletion of CLL cells in whole blood assays and the superior efficacy of GA-101 compared to rituximab [24].…”
Section: Ga-101mentioning
confidence: 99%
“…Type I display a potent ability to activate complement through enhanced recruitment of C1q [12] due to the efficient clustering of antibody Fc regions [13]; an activity directly linked to their ability to redistribute CD20 to lipid raft microdomains of the plasma membrane. In contrast, type II anti-CD20 mAb do not display either of these properties but instead evoke strong homotypic adhesion [14] and a non-apoptotic form of lysosomal cell death [14][15][16][17]. In addition, we observed that type I anti-CD20 mAb undergo more rapid internalization from the cell surface, in contrast to type II mAb [18][19][20].…”
Section: Introductionmentioning
confidence: 98%